Who do you love eaudiobook A novel. - Weiner, Jennifer (Simon & Schuster Audio, 2015)
#1 New York Times bestselling author Jennifer Weiner delivers "a tale of love against the odds" ( People). Rachel Blum and Andy Landis are just eight years old when they meet one night in an ER waiting room. Born with a congenial heart defect, Rachel is a veteran of hospitals, and she's intrigued by the boy who shows up alone with a broken arm. He tells her his name. She tells him a story. After Andy's taken back to a doctor and Rachel's sent back to her bed, they think they'll never see each other again. Yet, over the next three decades, Andy and Rachel will meet again and again—linked by chance, history, and the memory of the first time they met, a night that changed both of their lives. A sweeping, warmhearted, and intimate tale, Who Do You Love is an extraordinary novel about the passage of time, the way people change and change each other, and how the measure of a life is who you love.